Iris color distribution in the United States of America - Faris Hashem; Cristina Menicacci; David B. Granet (PLoS ONE, 2025)
Objective To document the distribution of iris color in the United States of America. Design This original investigation is an epidemiologic assessment of eye color data from all 50 states’ Department of Motor Vehicles (DMV). Participants All driver’s license holders data nationwide (age 16 years and older, both genders) were requested from the Department of Motor Vehicles (DMVs) in each state. Driver’s license holders from states whose DMV did not participate in the study due to special state-specific regulations, did not compile iris color information, or did not respond were then excluded. Main Outcome Measures Self reported eye color information was obtained from the DMVs databases of each driver’s license applicant self-reported eye color information. Methods All 50 states’ Department of Motor Vehicles in the USA were contacted using various methods and the database of driver licenses eye color for current active licenses (without including any personal information) was requested. Any iris color beyond grey, blue, green, hazel, or brown/black was categorized as “others”. Results Iris color of 235,423,085 driver’s license holders (DLHs) from 31 states was collected. The data show that brown/black iris color was documented in 124,811,254 DLHs (53%), blue in 55,797,458 DLHs (23.7%), hazel in 24,152,854 DLHs (10.3%), green in 21,258,873 DLHs (9%), grey in 1,597,675 DLHs (0.7%), and other iris colors in 7,804,971 DLHs (3.3%). Conclusions Utilizing information from over 230 million driver’s license holders, this report is the largest study of iris color distribution representing the United States of America, thus providing a valuable source for future eye disease and other sociological research. The data show that the most prominent iris color in the United States of America is brown/black, then blue, hazel, green, other iris colors, and grey.